Mucosal Herpes Immunity and Immunopathology to Ocular and Genital Herpes Simplex Virus Infections - Aziz Alami Chentoufi; Lbachir BenMohamed (Clinical and Developmental Immunology)
Herpes simplex viruses type 1 and type 2 (HSV-1 and HSV-2) are amongst the most common human infectious viral pathogens capable of causing serious clinical diseases at every stage of life, from fatal disseminated disease in newborns to cold sores genital ulcerations and blinding eye disease. Primary mucocutaneous infection with HSV-1 & HSV-2 is followed by a lifelong viral latency in the sensory ganglia. In the majority of cases, herpes infections are clinically asymptomatic. However, in symptomatic individuals, the latent HSV can spontaneously and frequently reactivate, reinfecting the muco-cutaneous surfaces and causing painful recurrent diseases. The innate and adaptive mucosal immunities to herpes infections and disease remain to be fully characterized. The understanding of innate and adaptive immune mechanisms operating at muco-cutaneous surfaces is fundamental to the design of next-generation herpes vaccines. In this paper, the phenotypic and functional properties of innate and adaptive mucosal immune cells, their role in antiherpes immunity, and immunopathology are reviewed. The progress and limitations in developing a safe and efficient mucosal herpes vaccine are discussed.